The Identification of Mycobacterium Tuberculosis in Active Smokers with Ziehl–Neelsen Staining Method - Hasanuddin, Asni; Jurnal Syarif; Dita Ellyana Artha (International Journal of Public Health Excellence (IJPHE), 2022)
Tuberculosis is still a health problem for the people of Indonesia, especially active smokers. There are many risk factors that can cause tuberculosis in active smokers including age at starting smoking, number of cigarettes consumed per day, and how long smoking has been done. The purpose of this study was to determine the results of identifying mycobacterium tuberculosis in active smokers with the Ziehl–Neelsen staining acid resistance test method. This type of research is a descriptive-analytic study that aims to determine the results of identifying Mycobacterium tuberculosis in active smokers. The Ziehl–Neelsen staining acid resistance test was conducted at the Tourism Hospital Laboratory of the University of East Indonesia Makassar on September 22 to October 6, 2022. The population in the study is 10 people. The sample was determined using a total sampling technique so that 10 samples were obtained. The research variables were active smokers. The data obtained are presented in the form of tables and narratives. After laboratory testing using the Ziehl–Neelsen staining method, the conclusion was that 1 out of 10 samples of active smokers was identified as Mycobacterium Tuberculosis.